Factors Influencing College Students’ Choice of Takeout Vendors –Study in Chengdu, China - Qiu, Jun; Kim, Seongdok (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
In today’s increasingly fierce competition in the catering industry, the takeout industry also develops rapidly. More and more catering enterprises begin to pay attention to catering delivery. According to the delivery data show that some vendors sell more takeout food than they do in brick-and-mortar stores. Takeout greatly meets the needs of college students, who therefore become the mainstream group in the takeout industry in China. At present, there are various forms in the takeout market, so it is particularly important to study the factors affecting college students’ choice of takeout vendors.Based on the Theory of Consumer Behavior and Technology Acceptance Model and previous research review,four factors are identified which are User Review,Price,Delivery Time,and Business Service that influence college students’ consumption behavior.Target population is Chinese college students in Chengdu city, China.384 survey questionnaire were collected via online using convenience and snowball sampling.Descriptive statistics and inferential statistics were utilized to describe demographic characteristics and do hypotheses testing. The results showed that user reviews, delivery time, and business service selection had significant effects.According to the research model and conclusion, suggestions are put forward for the development of takeout vendors in college students’ market.